2022
DOI: 10.1021/acsami.2c03707
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Binder with High-Affinity for the SARS-CoV-2 Spike Receptor-Binding Domain

Abstract: Rapid antigen detection tests are urgently needed for the early diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The discovery of a binder with high affinity and selectivity for the biomarkers presented by SARS-CoV-2 is crucial to the development of the rapid antigen detection method. We utilized the surface biopanning to identify a peptide binder R1 from a phage-displayed peptide library consisting of 10 9 independent phage recombinants. The R1 peptide exhibited high-affinity for spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…K D value is inversely proportional to the concentration of bound species. 32 The binding affinities of Rituximab were similar to the control upon addition of glucose in varying concentrations, as listed in Table 2. Similar K D values indicated no change in the affinity for the ligand protein that is, FcγRIIIA.…”
Section: Binding Of Rituximab To Fcγriiia By Surface Plasmon Resonancementioning
confidence: 67%
See 1 more Smart Citation
“…K D value is inversely proportional to the concentration of bound species. 32 The binding affinities of Rituximab were similar to the control upon addition of glucose in varying concentrations, as listed in Table 2. Similar K D values indicated no change in the affinity for the ligand protein that is, FcγRIIIA.…”
Section: Binding Of Rituximab To Fcγriiia By Surface Plasmon Resonancementioning
confidence: 67%
“…The reported affinity constant value of Rituximab for this variant was similar to the value reported by Dekkers et al 31 The increased K D values indicated decreased affinity for the ligand protein that is, FcγRIIIA. K D value is inversely proportional to the concentration of bound species 32 …”
Section: Resultsmentioning
confidence: 99%
“…Finally, Nsp13 is a helicase, that unwinds the RNA and promotes efficient transcription 25 , while Nsp15 serves as a uridine-specific endoribonuclease that facilitates the evasion of the host immune response 26 . Of the SARS-CoV-2 proteins, peptide binding has previously been shown for S receptor binding domain 27 , 28 , Nsp3 Ubl1 11 , 29 , Nsp5 30 , and suggested for Nsp10 31 , Nsp14 32 , and Nsp16 33 based on computational analysis. Furthermore, a potential peptide binding site in Nsp9 has been suggested from structural analysis 34 .…”
Section: Introductionmentioning
confidence: 97%
“…The SARS-CoV-2 spike glycoprotein S1 subunit mainly contains a receptor-binding domain (RBD) and an N -terminal domain (NTD). In fact, the RBD domain is responsible for engaging the human angiotensin-converting enzyme 2 (hACE2) receptors during viral infection and contains a wide range of neutralizing epitopes to effectively induce secretion of neutralizing antibodies to protect host cells from viral infection. , Therefore, the S1 subunit could be employed as an effective target in COVID-19 protein vaccines to elicit protective immune responses. …”
Section: Introductionmentioning
confidence: 99%
“…In fact, the RBD domain is responsible for engaging the human angiotensinconverting enzyme 2 (hACE2) receptors during viral infection and contains a wide range of neutralizing epitopes to effectively induce secretion of neutralizing antibodies to protect host cells from viral infection. 37,38 Therefore, the S1 subunit could be employed as an effective target in COVID-19 protein vaccines to elicit protective immune responses. 39−41 In this work, we prepared a novel Mn 3 (PO 4 ) 2 •3H 2 O nanoparticle (nano-MnP) by simply optimizing the ratio of Na 2 HPO 4 and NaH 2 PO 4 in MnCl 2 solution for the first time.…”
Section: ■ Introductionmentioning
confidence: 99%